STRUCTURAL AND FUNCTIONAL MODEL OF THE STOCK-RAISING TERRITORY ON THE ECOLOGICAL BASIS (ON THE EXAMPLE OF STAVROPOL) - Elena V. Pismennaya; Vladimir A. Stukalo; Elena А. Grudeva (Юг России: экология, развитие, 2018)
The leading sector of the South of Russia is crop production and livestock-raising with a relatively high risk. Animal husbandry in the region is facing a crisis; the structure and size of herds have sharply decreased. The cost of livestock products and the gap in the rate of its growth are constantly growing. There were problems with fodders and their structural and nutritional imbalance. There is a shortage of meat and dairy products. The volume of gross production for the period from 2005 to 2013 is provided by domestic and foreign meat imports which increased 3-fold. Methods. An analytical study on the state of animal husbandry is conducted on the basis of reports and statistical materials. The system "natural resource potential – industry sector" is described. Analysis of the current state of the industry is aimed at determining the methods of making decisions on land use management on the example of the structural and functional model of development of the agricultural enterprises. Results. At the present time, conditions arise when it is necessary to shift to a new scientifically grounded structural and functional model of the spatial organization of the enterprises. This will allow implementing the strategy of ecoadaptive intensification of grassland production, since the value of cultivated pastures is determined by high proportion of forage grasses in the feed balance and their huge ecological function. Conclusion. This structural and functional approach is based on the consolidation of the territory of agrarian enterprises and the phased subsequent replacement of biological species with different life cycle duration. In this case, the result is the rapid achievement of the maximum productivity of species with low competitive ability which will lead to short payback period.